A Disposable SWCNTs/AuNPs-Based Screen-Printed ISE at Different Temperatures to Monitor Ca2+ for Hypocalcemia Diagnosis - Zhixue Yu; Hui Wang; Yue He; Ruipeng Chen; Xiangfang Tang; Benhai Xiong (Chemosensors)
In this paper, screen-printed ion-selective electrodes combined with single-walled carbon nanotubes (SWCNTs) and gold nanoparticles (AuNPs) were used to rapidly and accurately measure serum Ca2+ concentration. Due to the susceptibility of cows to hypocalcemia after delivery, this disease can affect the health of cows and reduce milk production. Therefore, the development of an economical and swift detection method holds paramount importance for facilitating early diagnosis and subsequent treatment. In this study, by combining the high electrical conductivity and large surface area of SWCNTs with the strong catalytic activity of AuNPs, a SWCNTs/AuNPs composite with high sensitivity and good stability was prepared, achieving efficient selective recognition and signal conversion of Ca2+. The experimental results indicate that the screen-printed electrode modified with SWCNTs/AuNPs exhibited excellent performance in the determination of Ca2+ concentration. Its linear response range is 10−5.5–10−1 M, covering the normal and pathological concentration range of Ca2+ in cow blood, and the detection limit is far below the clinical detection requirements. In addition, the electrode also has good anti-interference ability and fast response time (about 15 s), showing good performance in the range of 5–45 °C. In practical applications, the combination of the electrode and portable detection equipment can realize the field rapid determination of cow blood Ca2+ concentration. This method is easy to operate, cost-effective, and easy to promote, providing strong technical support for the health management of dairy farms.